Discovery of a novel tricyclic 4H-thiazolo[5′, 4′:4, 5]pyrano[2, 3-c]pyridine-2-amino scaffold and its application in a PI3Kα inhibitor with high PI3K isoform selectivity and potent cellular activity. Issue 17 (1st September 2015) - Gerspacher, Marc; Fairhurst, Robin A.; Mah, Robert; Roehn-Carnemolla, Esther; Furet, Pascal; Fritsch, Christine; Guthy, Daniel A.
Graphical abstract